(untitled) (Journal of Mechanical Engineering, 2014)
All the key features, functions, characteristics, and spirit of a design are needed for a full concept for a product. Moreover, every product serves a certain purpose; if a product cant serve its purpose, then its useless. This is the basis of design, though it can hardly be evaluated and coped with properly. This type attribute is called must-be attribute. Thus, Many trouble occur if Must design is ignored; consequently design cannot provide a design warranty. Thus, computational tools are needed to assist a product development team to determine beforehand the critical number of respondents to make a right decision. In this regard, absolutely this paper presents a Kano model based customer needs simulation system for investigating must-be attribute. DOI: http://dx.doi.org/10.3329/jme.v44i1.19500